The dual danger of pyometra and endometrial carcinoma: a case report - Dayang Corieza Febriany; Mohamed Arif Hameed Sultan; Zubair Ahmad Sharifuddin; Anand Raj Thangavelu; Cindy Chin (Ital J Gynaecol Obstet, 2024)
Background. Pyometra, a collection of purulent material within the endometrial cavity, is a relatively uncommon gynaecological condition. Spontaneous perforation of the uterus is an infrequent complication of pyometra, most often the result of malignant conditions in the uterus. Case presentation. We report the case of an elderly woman who had acute abdominal pain due to a ruptured uterus secondary to pyometra resulting from an infected endometrial mass diagnosed on computed tomography. She underwent an urgent exploratory laparotomy, and a total hysterectomy and bilateral salpingo-oophorectomy were performed. Her CA-125 level was raised (102.3 U/ml) and the histopathological examination (HPE) of the endometrial mass confirmed an endometrial carcinoma. The rest of the HPE shows necrotic and inflamed perforated uterus and pyometra. No organism growth was detected in both endometrial or peritoneal pus cultures. Postoperatively, she received intravenous antibiotics and gradually recovered and discharge well. Conclusions. When an elderly post-menopausal patient presented with an acute abdomen, the possibility of a ruptured uterine perforation secondary to pyometra needs to be considered and the cause of this condition needs to be further investigated.